Medical Practitioners And The Evolution Of The Healthcare System In Saudi Arabia: A Detailed Review (The Review of Diabetic Studies, 2025)
Healthcare professionals are essential to effective health systems. They deliver services, promote health, prevent disease, and keep the system sustainable. In Saudi Arabia, the healthcare sector has changed significantly due to shifts in population, disease patterns, and national priorities. Vision 2030 has brought major changes, focusing on quality, efficiency, access, and patient-focused care. This article examines the Saudi healthcare system, highlighting the roles and impact of medical practitioners such as doctors, nurses, pharmacists, allied health workers, public health experts, and administrators. It also discusses staffing challenges, teamwork across professions, and future directions for healthcare in Saudi Arabia.